KAYU MINDI SEBAGAI RAW MATERIAL PEMBUATAN CASING TEKNOLOGI INFORMASI - Sumino Sumino; Achmad Gilang Romadhon (Institut Seni Indonesia Yogyakarta, 2021)
The use of solid teak wood has always been the choice of casing manufacturers for communication technology tools. This type of teak wood has the requirements for durable class and maximum strength class. Other types of wood are considered less qualified, one type of wood is Mindi wood, whereas Mindi wood actually looks beautiful. In the digital era, various forms of manufacturing casings made of plastic are offered, of course, plastic materials have a negative impact on the environment and seem cheap. Wood is a solution for providing materials in the manufacture of environmentally friendly casings of exclusive value. In order to achieve an exclusive concept in the era of fashion trends, the right method is needed in its cultivation, so this design uses a method that includes several stages, including, a) Observation and analysis stage, b) The imagination stage consists of exploration and experimentation of techniques and materials. , c) The stage of developing the imagination which is focused on the maturation of the concept as a result of the evaluation of the problem, d) The stage of implementing the design decisions that are ready to be worked on. The above method is then called the method of creating Practice-Ied Research. The design achievements along with the current trend and fashion era emphasize the character and contemporary lifestyle, but will also display a sentimental character that seems nostalgic for the past. Tend to accentuate the ancient and exclusive impression that offers the uniqueness of the wood grain, this is often referred to as a retro style product.Penggunaan kayu untuk produk industri saat ini telah nyata mendukung peningkatan Produk Domestik Bruto (PDB) dari sektor non minyak. Hal demikian ditandai dengan maraknya beragam produk estetis ataupun fungsional oleh pelaku bisnis berbahan kayu. Sebagian besar para pelaku mengacu pada trend dan fashion yang mencerminkan karakter dan gaya hidup kekinian, tetapi jarang sekali menampilkan karakter sentimentil yang seolah-olah bernostalgia ke masa lalu. Penggunaan kayu jati solid kelas satu selalu menjadi pilihan sehingga mengabaikan kayu-kayu yang lain, padahal kayu Mindi justru tampak sifat lokalitasnya, sehingga cenderung menonjolkan kesan kuno dan eklusif yang menawarkan keunikan serat kayu. Guna menuju pencapaian konsep kuno diperlukan sejumlah experiment dan metode yang tepat dalam penggarapannya, yakni: a) Tahap observasi dan analisis, b) Tahap imajinasi, c) Tahap pengembangan imajinasi, d) Tahap implementasi. Metode tersebut kemudian disebut dengan metode penciptaan Practice-Ied Research. Perancangan ini akan merealisasikan disain-disain kebaruan yang meliputi Commercial Casing untuk produk Information Technology.